Conexão entre matemática e música: um percurso para o estudo dos números racionais - Azevedo, Adalberto Tomaz de (2019)
This research aimed at presenting a teaching-learning process for a 6th grade group from Elementary School involved with the teaching of rational numbers, especially fractions. The approach of this school content involved the connection with the music, constituting an unconventional educational strategy. Based on the theoretical-methodological contributions of Raymond Duval, the development of this research was guided by the following research question: how does the insertion of music into the teaching-learning process of rational numbers contribute to the mobilization of the registers of semiotic representation? In order to support the methodological option of a descriptive and interpretive qualitative research, we present historical aspects and elements of musical theory in the course of the writing of the research report, as subsidies to explore the didactic-pedagogical potentiality of the mathematical and music connection in the study of the school content already mentioned. In the context of the public school of the State of São Paulo, in which the Teacher's Notebook is a material to support the development of skills and abilities prescribed in the official curricular document, it was prepared by the teacher-researcher the teaching-learning proposal systematized in six tasks described and analyzed from the written productions and interlocutions occurred to his students during the mathematics classes. We present to the reader the experience provided by this connection between different areas of knowledge, its contributions and suggestions to teachers interested in this educational possibility for the study of rational numbers.The usage of music in this teaching proposal permitted a more efficient and comprehensive learning with the coordination and use of different semiotic registers concerning the rational number occurring in a natural and meaningful way.